Sprint speed vs. swimming power - Costill, D. L.; King, D. S.; Holdren, A.; Hargreaves, M. (Swimming Technique, 1983)
Swimmers were tested using a tethered isokinetic force measuring device that allowed forward progress, rather than maintaining a static position, while freestyle swimming. The amount of work, peak force, and duration of test was recorded. It was found that small differences in sprinting speed were associated with measurable differences in swimming power and peak force. Implication: The application of power in sprint swimming is important. Therefore, the technique of sprinting should be a primary focus of training. Ultra-short training would appear to be the training form that would accommodate practicing race-pace sprinting form.